2019
DOI: 10.1111/bjh.15923
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre retrospective study of intravascular large B‐cell lymphoma treated at academic institutions within the United States

Abstract: Summary Intravascular large B‐cell lymphoma (IVLBCL) is a rare entity, with a generally aggressive course that may vary based on geographic presentation. While a United States (US) registry study showed relatively good outcomes with IVLBCL, clinicopathological and treatment data were unavailable. We performed a detailed retrospective review of cases identified at 8 US medical centres, to improve understanding of IVLBCL and inform management. We compiled data retrieved via an Institutional Review Board‐approved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…This emphasizes that skin biopsy, particularly random skin biopsy, which is a minimally invasive method, appears to be a useful diagnostic tool even in the absence of BM invasion and sometimes can preclude unnecessary biopsy of other vital organs. Therefore, we agree with previous reports that [9][10][11][12][13][14]. Sections from the lower extremities and trunk are important and may yield a better chance to detect lymphoma cells since our results suggest that cutaneous lesions in IVLBCL commonly affected these areas.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This emphasizes that skin biopsy, particularly random skin biopsy, which is a minimally invasive method, appears to be a useful diagnostic tool even in the absence of BM invasion and sometimes can preclude unnecessary biopsy of other vital organs. Therefore, we agree with previous reports that [9][10][11][12][13][14]. Sections from the lower extremities and trunk are important and may yield a better chance to detect lymphoma cells since our results suggest that cutaneous lesions in IVLBCL commonly affected these areas.…”
supporting
confidence: 92%
“…Nonetheless, random skin biopsy (RSB) has been proposed as a useful diagnostic tool in IVLBCL by Gill et al [7]. Subsequent studies also confirmed the potential of RSB in establishing the diagnosis of IVLBCL [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…21 Before being listed in the WHO classification, IVLBCL reports from the USA were extremely limited, but a retrospective study from academic centers in the USA has been recently reported. 27 In respectively. 27 Although skin eruption and neurological symptoms were more common in the USA than in Japan, the clinical aggressiveness of IVLBCL did not differ much (Table 1).…”
Section: Clini C Al Char Ac Teris Ti C S Of Ivlbclmentioning
confidence: 99%
“…27 In respectively. 27 Although skin eruption and neurological symptoms were more common in the USA than in Japan, the clinical aggressiveness of IVLBCL did not differ much (Table 1).…”
Section: Clini C Al Char Ac Teris Ti C S Of Ivlbclmentioning
confidence: 99%
“…2,3 Remarkably, the blood vessel is the site of active cell replication and also serves as vehicle for disease spread. The clinical manifestations of IVLBCL are extremely heterogeneous, and the disease is frequently regarded as a great imitator, which poses diagnostic challenges, 3,4 but increasing clinical awareness of it has steadily improved recognition and diagnosis. 5 A skin biopsy is generally used to reach a diagnosis in cutaneous IVLBCL and in a fraction of patients with the classical variant of the disease.…”
mentioning
confidence: 99%